Analysıs Of The Effect Of Middle East Energy Resources On Economic Growth Of The Countries In The Region - Bayraç, Hüseyin Naci; Çemrek, Fatih (Fırat University, 2022)
The oil crises that emerged in 1973 and 1979 and the resulting price increases made energy, especially oil, one of the most important factors of growth in the world economy. There is a very close relationship between the economic growth levels of countries and the amount of energy demand and consumption. Despite the increasing dependence and demand on energy, energy reserves are depleting rapidly. This situation has led to an increase in the interest in the Middle East region, where approximately 48% of the world's oil reserves and 40% of natural gas reserves are located. The oil and natural gas reserves and production amounts of the Middle East have the most important place in the economic growth of the countries in the region. In the study, the reserves, production and consumption levels of oil and natural gas in the Middle East region and the effects of these resources on the regional economies are discussed. In the analysis phase, the relationship between oil production and economic growth for Iran, Iraq, Kuwait, Oman, Qatar, Saudi Arabia, Syria, UAE and Yemen, which are important oil producers in the Middle East Region, was investigated by panel data analysis. According to the analysis result; An increase in oil production by 1% causes a 0.9% increase in economic growth. The oil reserves and production amounts of the Middle East have the most important place in the economic growth of the countries in the region.

1973 ve 1979 yıllarında ortaya çıkan petrol krizleri ve buna bağlı oluşan fiyat artışları, dünya ekonomisinde başta petrol olmak üzere, enerjiyi büyümenin en önemli faktörlerinden birisi konumuna getirmiştir. Ülkelerin ekonomik büyüme düzeyleri ile enerji talep ve tüketim miktarları arasında çok yakın bir ilişki vardır. Enerjiye olan bağımlılığın ve talebin giderek artmasına karşın, enerji rezervleri de hızlı bir şekilde tükenmektedir. Bu durum dünya petrol rezervlerinin yaklaşık % 48’inin ve doğalgaz rezervlerinin ise, % 40’ının yer aldığı Orta Doğu bölgesine olan ilginin artmasına neden olmuştur. Orta Doğu’nun sahip olduğu petrol ve doğalgaz rezervleri ve üretim miktarları, bölge ülkelerinin ekonomik büyümesinde en önemli bir yere sahiptir. Çalışmada, Orta Doğu bölgesindeki petrol ve doğalgazın rezerv, üretim ve tüketim düzeyleri ve bu kaynakların bölge ekonomilerine olan etkileri ele alınmaktadır. Analiz aşamasında, Orta Doğu Bölgesi’ndeki önemli petrol üreticileri olan İran, Irak, Kuveyt, Umman, Katar, Suudi Arabistan, Suriye, BAE, Yemen için petrol üretimi ve ekonomik büyüme arasındaki ilişki panel veri analizi ile araştırılmıştır. Analiz sonucuna göre; petrol üretiminin % 1 oranında artması, ekonomik büyüme üzerinde % 0.9’luk bir artışa neden olmaktadır. Orta Doğu’nun sahip olduğu petrol rezervleri ve üretim miktarları, bölge ülkelerinin ekonomik büyümesinde en önemli bir yere sahiptir.
ORTA DOĞU ENERJİ KAYNAKLARININ BÖLGE ÜLKELERİNİN EKONOMİK BÜYÜMESİ ÜZERİNDEKİ ETKİSİNİN ANALİZİ